Manutenção do banco de plântulas em diferentes bosques de mangue na foz do rio Itaúnas, Conceição da Barra, Espírito Santo, Brasil - Lima, Karen Otoni de Oliveira (2014)
Mangroves have global distribution within regions of tropical and subtropical climates, providing a range of environmental and socio-economic goods and services. The impacts caused by the human population and, more recently, the shifts that will be caused by global climatic changes are topics of extreme interest to the scientific community. Faced with this future perspective, understand the ecological characteristics of the establishment and maintenance of mangrove seedlings becomes necessary, since the energies subsidiaries that operate on this system occur at different spatial and temporal scales. Ecology of seedlings dynamic require long-term studies because important processes would be masked once them could occur slowly, so when time series of ecological analyzes are magnified in scientific program, development processes become more explicit. This study was conducted in the mangrove at the mouth of the Itaúnas river, protected by Itaúnas State Park in Conceição da Barra, Espírito Santo. In the mangrove three plots were demarcated in January 2008 along with the collection of data structure. Monitoring occurs since then, and monthly we have monitoring the density of seedlings, collected dates of salinity, temperature and precipitation. The integrated analysis of temporal population data is being conducted to determine which periods occurs higher mortality and ingress of seedling. Subsequently, we correlated these structural data with the environmental factors which affect the seedllings dynamics. These analyzes, we found that each cohort shows differences in density of ingress, survival and mortality of seedlings and may be related mainly to the accumulation of precipitation periods before the production of flowers and fruits of the forest. Also interpret that the species intrinsic factors regulate the establishment and seedling viability. This data series contributed to determining patterns of entry and survival of different species studied, allowing for the ecological diagnosis of mangrove forest in Espirito Santo coast. The recognition of the processes that prevail in each mangrove forest studied is essential to meet their development, this will contribute to appropriate actions for conservation and management.